Assessment of users’ behavior in Lithuanian online communities - Skarzauskiene, Aelita; Mačiulienė, Monika (Frontiers in Psychology, 2023)
Introduction Online communities are gaining importance in modern society by actively structuring public opinion and initiating discussions about various socio-economical issues. As information and communication technologies advance, the online communities are confronted with novel technological and societal hurdles (the spread of misinformation, lack of active participation). To boost their efficacy and productivity, it’s crucial to enhance our understanding of user behavior, communication avenues and potential future trends of development. Objective Online platforms serve a function beyond simply sharing information or knowledge; they act as influential social networks affecting various societal sectors, including politics, culture and the economy. There is a need to recognize online communities not as static entities, but as dynamic, evolving systems of collective intelligence. Methods A representative quantitative study was carried out between 1 to 30 of October 2022 through direct, in-person interviews conducted at the respondent’s residence (known as an Omnibus survey). The sample of respondents is representative of the entire population of Lithuania regarding essential socio-demographic characteristics. By thoroughly analyzing data gathered from a comprehensive quantitative study, the study raises awareness of the issues surrounding online communities, while also shedding light on social networking behavior within these virtual spaces. Discussion Despite the multitude of challenges inherent to virtual communication, there remains a significant knowledge gap in comprehending general user behavior within these online communities. The current research aims to bridge this gap by investigating user behavior in Lithuanian online communities.